Attitudes and Preferences towards Self-help Treatments for Depression in Comparison to Psychotherapy and Antidepressant Medication. Issue 2 (20th February 2015) - Hanson, Katie; Webb, Thomas L.; Sheeran, Paschal; Turpin, Graham
Abstract : Background: Self-help is an effective treatment for depression. Less is known, however, about how acceptable people find different self-help treatments for depression.Aims: To investigate preferences and attitudes toward different self-help treatments for depression in comparison to psychotherapy and antidepressants.Method: N = 536 people who were not actively seeking treatment for depression were randomly assigned to read about one of five treatment options (bibliotherapy, Internet-based self-help, guided self-help, antidepressants, or psychotherapy) before rating how acceptable they found the treatment. Participants also ranked the treatments in order of preference.Results: Psychotherapy and guided self-help were found to be the most acceptable and preferred treatment options. Antidepressants and bibliotherapy were found to be the least acceptable treatments, with antidepressants rated as the most likely to have side effects. Preference data reflected the above findings – psychotherapy and guided self-help were the most preferred treatment options.Conclusions: The findings highlight differences in attitudes and preferences between guided and unguided self-help interventions; and between self-help interventions and psychotherapy. Future research should focus on understanding why unguided self-help interventions are deemed to be less acceptable than guided self-help interventions for treating depression.